The Complement Binding and Inhibitory Protein CbiA of Borrelia miyamotoi Degrades Extracellular Matrix Components by Interacting with Plasmin(ogen) - Nguyen, Ngoc T. T.; Röttgerding, Florian; Devraj, Gayatri; Lin, Yi-Pin; Koenigs, Arno; Kraiczy, Peter (Frontiers in Cellular and Infection Microbiology, 2018)
The emerging relapsing fever spirochete Borrelia (B.) miyamotoi is transmitted by ixodid ticks and causes the so-called hard tick-borne relapsing fever or B. miyamotoi disease (BMD). More recently, we identified a surface-exposed molecule, CbiA exhibiting complement binding and inhibitory capacity and rendering spirochetes resistant to complement-mediated lysis. To gain deeper insight into the molecular principles of B. miyamotoi-host interaction, we examined CbiA as a plasmin(ogen) receptor and potential adhesin that enables B. miyamotoi to interact with the serine protease plasmin(ogen) and also adhere to the mouse brain endothelial cells. Recombinant CbiA was able to bind plasminogen in a dose-dependent fashion. Moreover, lysine residues appear to play a crucial role in the protein-protein interaction as binding of plasminogen was inhibited by the lysine analog tranexamic acid as well as increasing ionic strength. Of relevance, plasminogen bound to CbiA can be converted by urokinase-type plasminogen activator (uPa) to active plasmin which cleaved both, the chromogenic substrate S-2251 and its physiologic substrate fibrinogen. Concerning the involvement of specific amino acids in the interaction with plasminogen, lysine residues located at the C-terminus are frequently involved in the binding as reported for various other plasminogen-interacting proteins of Lyme disease spirochetes. Lysine residues located within the C-terminal domain were substituted with alanine to generate single, double, triple, and quadruple point mutants. However, binding of plasminogen to the mutated CbiA proteins was not affected, suggesting that lysine residues distant from the C-terminus might be involved in the interaction.